Survey of Patient Knowledge and Expectations about a Free-Standing Emergency Department. (13th September 2015) - Bucciarelli, Christopher; Payton, Thomas; Weeks, Emily; Falgiani, Michael
Abstract : Objectives . A free-standing emergency department (FSED) is defined as a facility that is structurally separate and distinct from a hospital and provides emergency care. Nationally, the number of FSEDs continues to grow, but the general public may have limited knowledge about the costs and services associated with FSEDs. The purpose of this paper is to survey patient knowledge and expectations about FSEDs. Methods . A convenience sample of patients presenting to a FSED was given a 19-item survey to complete. Results . 187 surveys were collected; 126 were included for analysis. 40% of respondents thought they could be seen by a specialist at the FSED, and 55% of patients did not know they had to be transferred for hospitalization if required. Most patients did not know that the cost of services at the FSED would be the same as that at the traditional ED. Convenience and perceived shorter wait times were the primary reasons patients selected the FSED for care. Conclusion . In general, patients do not have adequate knowledge about the costs and services associated with FSEDs. Education through marketing and advertising may be helpful in creating more public awareness about FSEDs.